Taxonomic history of Meistera acuminata (Thwaites) Škorničk. & M.F.Newman (Zingiberaceae) with notes on typification, affinities and variations. Issue 2 (3rd July 2018) - Thomas, Valukattil Ponnachan; Sabu, Mamiyil
ABSTRACT: A new synonym Meistera muricata is proposed for M. acuminata . The nomenclatural and identity confusions were resolved with typification in this paper. Detailed descriptions, illustration, photographs, etc. are provided. The affinities and variations of specimens are also discussed.